2017
DOI: 10.1111/jpn.12813
|View full text |Cite
|
Sign up to set email alerts
|

2‐Hydroxy‐4‐methylthio butanoic acid and DL‐methionine for Japanese quails in production

Abstract: An experiment was performed using 1,000 laying Japanese quails to assess the availability of two alternative dietary methionine sources. Treatment 01 = Basal Feed that is deficient in digestible methionine + cystine (Met + Cys). The other treatments were constituted by Met + Cys levels of 0.8, 1.60 and 2.40 g/kg, supplemented with DL-Methionine-99%, HMTBA-88% and HMTBA-84%, being 10 treatments in total. The following characteristics were studied: feed intake (g/bird/day), egg production (egg/day × 100), egg we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Previous studies showed that Met deficiency in poultry reduced growth, feed intake (FI), body weight gain (BWG), egg size, production and increased feed conversion ratio (FCR) for layers and breeders ( 12 14 ). Additionally, low methionine diets decrease laying performance and egg quality ( 15 , 16 ). Moreover, a deficiency of Met in the diet of laying hens impairs the whole-body protein metabolism, significantly reducing protein synthesis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Met deficiency in poultry reduced growth, feed intake (FI), body weight gain (BWG), egg size, production and increased feed conversion ratio (FCR) for layers and breeders ( 12 14 ). Additionally, low methionine diets decrease laying performance and egg quality ( 15 , 16 ). Moreover, a deficiency of Met in the diet of laying hens impairs the whole-body protein metabolism, significantly reducing protein synthesis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Se tratando de uma cultura de fácil manejo (Pastore et al, 2012) e rápido retorno financeiro (Silva et al, 2018), pequenos produtores tem buscado se incluir nesse mercado (Albino e Barreto, 2003). O sucesso na produção se dá pelo avanço no conhecimento em diversas frentes de pesquisa em métodos que avaliem a nutrição de codornas (Silva et al, 2012;Rostagno et al, 2017) e têm aumentado de forma considerável, nos diferentes ramos, seja na determinação das exigências em energia (Silva et al, 2004a;Moura et al, 2008;Vieira et al, 2020a), proteína bruta (Silva et al, 2004b;Vieira et al, 2020b), aminoácidos (Vieira et al, 2018;Mauricio et al, 2018), minerais (Bezerra et al, 2011;Vieira et al, 2012;Lima et al, 2015) e balanço eletrolítico (Rodrigues et al, 2015;Vieira et al, 2015) e também nas busca de alimentos alternativos para as dietas (Pereira et al, 2016;Valentin et al,2019).…”
Section: Introductionunclassified